Triple-negative breast cancer modifies the systemic immune landscape and alters neutrophil functionality - Noor A. M. Bakker; Hannah Garner; Ewald van Dyk; Elisa Champanhet; Chris Klaver; Maxime Duijst; Leonie Voorwerk; Iris Nederlof; Rosie Voorthuis; Marte C. Liefaard; Marja Nieuwland; Iris de Rink; et al. (npj Breast Cancer)
Abstract Cancer disrupts intratumoral innate-adaptive immune crosstalk, but how the systemic immune landscape evolves during breast cancer progression remains unclear. We profiled circulating immune cells in stage I–III and stage IV triple-negative breast cancer (TNBC) patients and healthy donors (HDs). Metastatic TNBC (mTNBC) patients had reduced T cells, dendritic cells, and differentiated B cells compared to non-metastatic TNBC patients and HDs, partly linked to prior chemotherapy. Vδ1 γδ T cells from mTNBC patients produced more IL17 than those from HDs. Chemotherapy-naïve mTNBC patients showed increased classical monocytes and neutrophils. Transcriptional, proteomic, and functional analyses revealed that neutrophils in mTNBC exhibited enhanced migratory capacity, elevated granule proteins, and higher ROS production. Some immune changes, such as reduced non-switched B cells and heightened neutrophil migration, were evident in earlier TNBC stages. This study comprehensively maps systemic immunity in TNBC, guiding future research on patient stratification and immunomodulation strategies.